(untitled) (Journal of Science and Technology, 2016)
The poultry industry is perceived to be a major contributor to Ghana’s development through employment creation and the enhancement of nutrition and food security. In spite of these contributions, the poultry industry is entangled with a number of problems that necessitate redress. The purpose of the study was to determine how activities within the poultry industry are operationalised, examine the prospects and challenges that confront the industry and make recommendations to inform policy. For the survey, 45 poultry farms and 10 major dealers of poultry inputs within the Dormaa District were randomly selected. Primary data were obtained through questionnaire administration, semi-structured interviews and observations. Secondary data on poultry farming were also obtained from the District Veterinary Services Division, the District Assembly and the Poultry Farmers’ Association. The survey revealed that the major challenges encountered by the poultry farmers included; financing, diseases and absence of electricity for operations in most farms (84.4%). The presence of feed processing mills, poultry input shops and availability of organised markets served as prospects that could be harnessed to boost the growth of the poultry industry in the district.